Injectable oligomer-cross-linked gelatine hydrogels via anhydride–amine-conjugation. Issue 9 (22nd February 2021) - Nawaz, Hafiz Awais; Schröck, Kathleen; Schmid, Maximilian; Krieghoff, Jan; Maqsood, Iram; Kascholke, Christian; Kohn-Polster, Caroline; Schulz-Siegmund, Michaela; Hacker, Michael C.
Abstract : Oligomer-cross-linked gelatine-based hydrogels are valuable tools for drug and cell delivery due to their extracellular matrix-like properties that can be adjusted by the composition of the oligomer and the degree of cross-linking. Abstract : Injectable gelatine-based hydrogels are valuable tools for drug and cell delivery due to their extracellular matrix-like properties that can be adjusted by the degree of cross-linking. We have established anhydride-containing oligomers for the cross-linking of gelatine via anhydride–amine-conjugation. So far, this conversion required conditions not compatible with cell encapsulation or in vivo injection. In order to overcome this limitation, we developed an array of quarter-oligomers varying in comonomer composition and contents of reactive anhydride units reactive towards amine groups under physiological conditions. The oligomers were of low molecular weight ( M n < 5 kDa) with a high degree of chemically intact anhydrides. Chemical comonomer composition was determined by 1 H-NMR. Dissolutions experiments confirmed improved hydrophilicity of the synthesized oligomers over our established compositions. Injectable formulations are described utilizing cytocompatible concentrations of constituent materials and proton-scavenging base. Degree of cross-linking and stiffness of injectable hydrogels were controlled by composition. The gels hold promise as injectable drug or cell carrier and as bioink.